PERCEPTION OF MSE’s MANAGERS AS THE APPLICATION OF HUMAN RESOURCES TOOLS - Tonny Kerley de Alencar Rodrigues; Atila de Melo Lira; Irenilza de Alencar Naas; Daniel Max de Sousa Oliveira (European Scientific Journal, ESJ, 2014)
People management is a major challenge to the MSEs of Teresina -PI due to the inability of management by some managers and their negligence before the adoption of management strategies that foster the development of its employees. In response to the reality which takes shape highlights the importance of the application of management tools that can assign value to the people who make up the company. This study was conducted in order to provide rational solutions to the following questions: what is the level of knowledge and application of micro and small entrepreneurs Teresina regarding people management tools? Notoriously has for objective measure knowledge of managers of MSEs Teresina-PI regarding people management tools and if they use these tools in their organizations. This is a survey with quantitative approach, characterized as exploratory and applied using as an instrument of data collection, a structured questionnaire consisting of seven statements based on Likert scale applied to 339 MSEs of Teresina. The results showed that managers are unaware and/or not applicable management tools and people often ignore elements deemed to be essential to manage these employees.